Launch : how to quickly propel your business beyond the competition - Stelzner, Michael A. (Hoboken, N.J. : John Wiley, 2011)
"Successful marketers share something in common-they produce engaging and interesting content that meets the insatiable demand for "how to" information. The best marketers don't need to sell themselves; instead, they demonstrate their expertise by the content they produce, the ideas they showcase, the success stories they share, and the people they attract. By giving a platform to other successful peers, marketers can build strategic alliances, quickly grow a large following, and dominate their industry. The book teaches how to successfully build your own platform through content marketing while praising and working with competitors. It teaches skills that when applied, will cause peers and industry power players to seek opportunities to partner with your business. The book explains how to(a) create excellent content OR talk about excellent content,(b) get content in front of the right people,(c) capture names and grow a following,(d) use leverage to build partnerships and relationships,(e) sell, and(f) repeat the process.Following a combination of the methods outlined in this book will bring you both a large community of potential customers as well as an understanding of how to best sell and promote yourself to this valuable group"--
Includes index.
Keywords: Marketing; Marketing -- Management; Customer relations -- Management; Business networks -- Management; Industrial promotion; BUSINESS & ECONOMICS / Marketing / General